2010
DOI: 10.1002/ajmg.b.31058
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of multiexonic deletion of the GCH1 gene in a Taiwanese cohort of dopa‐response dystonia

Abstract: Large deletions in the GCH1 gene have been reported in a minority of cases of dopa-responsive dystonia (DRD). In this study, we performed an extensive clinical and genetic investigation of 22 affected members in eight families. Sequence analysis revealed five different mutations in five families (n = 10); Ser81Pro (novel), Ser76X, Gly203Arg, 249del A, and IVS5 + 3insT. Applying multiple ligation-dependent probe amplification analysis, we detected a large heterozygous deletion of exons 1-3 in the remaining thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…[9][10][11][12][13] All patients in this analysis met the diagnosis criteria for DRD. 14 Each mutation was classified as a (1) missense mutation; (2) exon-intron boundary variant, that is, a variant located in an exon-intron boundary region; (3) large deletion,which can be deleted only by multiple ligation-dependent probe amplification analysis; or (4) small deletion, which can be detected only by direct sequencing.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…[9][10][11][12][13] All patients in this analysis met the diagnosis criteria for DRD. 14 Each mutation was classified as a (1) missense mutation; (2) exon-intron boundary variant, that is, a variant located in an exon-intron boundary region; (3) large deletion,which can be deleted only by multiple ligation-dependent probe amplification analysis; or (4) small deletion, which can be detected only by direct sequencing.…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…Clinical manifestations of DRD differ among families, and even among patients from the same family. 9 However, the clinical and genetic heterogeneity associated with the disease means that large number of DRD patients are needed in order to examine the correlations between phenotype and genotype, most studies to date have been conducted on relatively limited patient populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deletion frequency in European patients with DRD was reported to be approximately 8% (Hagenah et al, 2005;Zirn et al, 2008), which is not substantially higher than the 5.5% found in our study. However, another study based on Taiwanese subjects found a very high frequency of large heterozygous deletions (54% of total patients), although all patients carrying deletions were from three pedigrees and shared the same deletion (exons 1-3) (Wu-Chou et al, 2010). Two factors might contribute to the difference in frequencies observed between their study and ours: 1) more than half of the patients in our study were sporadic cases, whereas all of the patients in the Taiwanese study were familial cases; and 2) founder effects might exist in the Taiwanese study.…”
Section: Discussionmentioning
confidence: 93%
“…To investigate whether exonic deletions in GCH1 (or other DRD-related genes) contribute to the genetic background of DRD, we performed multiple ligation-dependent probe amplification analyses (MLPA) to search for plausible deletions. MLPA can be used to determine the copy number of up to 50 DNA sequences in a single multiplex polymerase chain reaction (PCR)-based reaction, and it has been widely employed for the detection of exonic deletions including within DRD (Furukawa et al, 2000;Klein et al, 2002;Hagenah et al, 2005;Steinberger et al, 2007;Wider et al, 2008;Zirn et al, 2008;Wu-Chou et al, 2010). In this study, we conducted MLPA analyses on three DRD pathogenic genes in Han Chinese DRD pedigrees and subjects with sporadic DRD to determine whether heterozygous exonic deletions could be found in addition to point mutations.…”
Section: Introductionmentioning
confidence: 99%